New Empirical Evidence on the Validity and the Reliability of the Early Life Stress Questionnaire in a Polish Sample - Sokołowski, Andrzej; Dragan, Wojciech Ł. (Frontiers in Psychology, 2017)
Background: The Early Life Stress Questionnaire (ELSQ) is widely used to estimate the prevalence of negative events during childhood, including emotional, physical, verbal, sexual abuse, negligence, severe conflicts, separation, parental divorce, substance abuse, poverty, and so forth. Objective: This study presents the psychometric properties of the Polish adaptation of the ELSQ. It also verifies if early life stress is a good predictor of psychopathology symptoms during adulthood. Method: We analyzed data from two samples. Sample 1 was selected by random quota method from across the country and included 609 participants aged 18-50 years, 306 women (50.2%) and 303 men (49.8%). Sample 2 contained 503 young adults (253 women and 250 men) aged 18-25. Confirmatory and exploratory factor analyses were used to measure ELSQ internal consistency. The validity was based on the relation to psychopathological symptoms and substance misuse. Results: Results showed good internal consistency and validity. Exploratory factor analysis indicates a six-factor structure of the ELSQ. Early life stress was related to psychopathology in adulthood, including depressive, sociophobic, agoraphobic, vegetative as well as pain symptoms. ELSQ score correlated also with alcohol use, but not nicotine dependence. Moreover, early life stress was correlated with stress in adulthood. Conclusions: The findings indicate that the Polish version of the ELSQ is a valid and reliable instrument for assessing early life stress in the Polish population and may be applied in both clinical and community samples.